1983
DOI: 10.1007/bf00252890
|View full text |Cite
|
Sign up to set email alerts
|

Functional and ultrastructural alterations of autologous platelets labeled with 111In-oxine

Abstract: High activity labeled platelets could be useful for the detection and observation of small foci of thrombosis by gamma-camera imaging. Therefore platelets were labeled with 111In-oxine containing increasing activities of 111In to determine the elimiting amount of this tracer that did not cause cell damage. A labeling procedure was employed so that all the chemical parameters remained constant except the amount of 111In. Platelet damage was studied by ADP-induced aggregability according to the Born procedure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The radioisotopic method used has been evaluated by several investigators. It has been shown that In-1 11 oxine is firmly bound to platelets and that dissociation of In-111 oxine from the platelets does not occur in viuo (29,30). I n addition, a previous study on platelet sequestration in the lungs and liver in sheep showed that gamma camera images correlated well with direct tissue activity measurements (25).…”
Section: Discussionmentioning
confidence: 89%
“…The radioisotopic method used has been evaluated by several investigators. It has been shown that In-1 11 oxine is firmly bound to platelets and that dissociation of In-111 oxine from the platelets does not occur in viuo (29,30). I n addition, a previous study on platelet sequestration in the lungs and liver in sheep showed that gamma camera images correlated well with direct tissue activity measurements (25).…”
Section: Discussionmentioning
confidence: 89%
“…HillZobel et al (;1987) used rabbit platelets labelled with indium-Ill oxine-sulphate, tropolone or MPO and re-ported on marked decreases in platelet survival and initial recovery in platelets labelled without plasma. With 7.4 MBq per 109 platelets labelled in saline, Bernard et al (1983) found only slight morphological alterations on scanning electron microscopy and also described about a 15% decrease in aggregability compared with unlabelled platelets. Other studies indicated unimpaired platelet survival with platelets labelled outside of plasma (Heaton et al 1979).…”
Section: Discussionmentioning
confidence: 93%
“…Earlier experiments have shown that Indium-Ill oxine is firmly bound to platelets and that dissociation of In-111 oxine from platelets does not occur in vivo [13][14][15]. Hence, the radioactivity measured in those organs (lung, liver, and kidney) reflects the number of platelets sequestered in those organs.…”
Section: Discussionmentioning
confidence: 97%